Post-crisis International Banking : An Analysis with New Regulatory Survey Data - Ichiue, Hibiki (IMF Working Papers; Working Paper, 2016)
Foreign bank lending has stopped growing since the global financial crisis. Changes in banks' business models, balance-sheet adjustments, as well as the tightening of banking regulations are potential drivers of this prolonged slowdown. The existing literature however suggests an opposite effect related to regulation, with tighter regulations encouraging foreign lending through regulatory arbitrage. We investigate this question using new survey data on regulations specific to banks' international operations. Our results show that regulatory tightening can explain about half of the decline in the foreign lending-to-GDP ratio between 2007 and 2013. Regulatory changes in home countries have had a larger effect than those in host countries.